Early onset mixed cryoglobulinemia in hepatitis C - Kritika Krishnamurthy; Sudhesna Mohapatra; T K Mishra; Nikhil Jha (Wolters Kluwer Medknow Publications, 2015)
Cryoglobulinemia is one of the most common forms of extrahepatic manifestation of chronic hepatitis infection. The phenomenon is generally seen after several years of chronicity predominantly in the female population resulting in arthralgias, purpuras, and other symptoms, due to vasculitis. Here we present a case of incomplete mixed cryoglobulinemia Type III (as per Brouet's classification) in a young boy aged 13 years who presented with an unusual symptom of pruritus. Diagnosis was confirmed by cryoprecipitation test followed by immunofixation. We aim to highlight the difficulty in diagnosis of this rare case/presentation, important investigation pitfalls and how to avoid them.